2019
DOI: 10.1186/s13104-019-4300-6
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between psychological distress and bullying victimisation among school-going adolescents in Ghana: a cross-sectional study

Abstract: Objective One of the pervasive problems in schools that has adverse implication on the wellbeing of students, is bullying victimisation. However, within sub-Saharan Africa, only few studies have examined how psychological distress influences bullying victimisation. The purpose of this study was to explore the association between bullying victimization and psychological distress among school going adolescents in Ghana. Results One hundred and ninety-eight (198) male and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
31
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 21 publications
8
31
1
1
Order By: Relevance
“…Being bullied, engagement in a physical fight, being physically attacked, and going hungry served as factors which increased the odds of experiencing psychosocial distress in our study. Bullying has, for instance, been established as one of the persistent difficulties in schools and it has negative consequences for the physical, social, and mental health of students such as suicidal ideation and depression [ 44 46 ]. Having close friends, however, decreased the odds of experiencing psychosocial distress among in-school adolescents in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Being bullied, engagement in a physical fight, being physically attacked, and going hungry served as factors which increased the odds of experiencing psychosocial distress in our study. Bullying has, for instance, been established as one of the persistent difficulties in schools and it has negative consequences for the physical, social, and mental health of students such as suicidal ideation and depression [ 44 46 ]. Having close friends, however, decreased the odds of experiencing psychosocial distress among in-school adolescents in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Items on the DASS-21 are scored on a three-point Likert scale ranging from 0 = does not apply to me at all to 3 = applies to me very much or most of the time. The reliability of the DASS-21 has been established within the Ghanaian context (Arhin, Oppong Asante, Kugbey, & Oti-Boadi, 2019 ; Asante, 2012 ). Since, the DASS-21 distinguishes between depression, anxiety and stress as distinct manifestations of psychological distress, the total of the subscales were used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The finding further showed that social support significantly predicted depression and stress while significant differences in all three in terms of sex. Arhin et al [15] studied anxiety, stress, and depression and bullying victimization among school-going adolescents. They found that psychological distress comprising depression, anxiety, and stress positively predicted bullying victimization among adolescent.…”
Section: Introductionmentioning
confidence: 99%